2017
DOI: 10.1002/acm2.12240
|View full text |Cite
|
Sign up to set email alerts
|

Automatic calculation of patient size metrics in computed tomography: What level of computational accuracy do we need?

Abstract: ObjectivesTo compare the effectiveness of two different patient size metrics based on water equivalent diameter (D w), the mid‐scan water equivalent diameter D w_c, and the mean (average) water equivalent diameter in the imaged region, D w_ave, for automatic detection of accidental changes in computed tomography (CT) acquisition protocols.MethodsPatient biometric data (height and weight) were available from a previous survey for 80 adult chest examinations, and 119 adult single‐acquisition chest–abdomen–pelvis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Unfortunately, unlike the observation that d w increases with age for the pediatric population [ 28 ], no significant correlation was observed between d w and age for chest and abdomen-pelvis CT, which is attributed to the lack of growth of d w with the increasing ages of adult patients. However, similar to previous results reported by Menke [ 20 , 25 ], we also found that both body weight and BMI strongly correlated with d w in chest and abdomen-pelvis, despite different populations in Asian-Pacific and European-American regions. Thus, age cannot be used to generate f for calculating SSDEs in adult patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Unfortunately, unlike the observation that d w increases with age for the pediatric population [ 28 ], no significant correlation was observed between d w and age for chest and abdomen-pelvis CT, which is attributed to the lack of growth of d w with the increasing ages of adult patients. However, similar to previous results reported by Menke [ 20 , 25 ], we also found that both body weight and BMI strongly correlated with d w in chest and abdomen-pelvis, despite different populations in Asian-Pacific and European-American regions. Thus, age cannot be used to generate f for calculating SSDEs in adult patients.…”
Section: Discussionsupporting
confidence: 92%
“…Sarmento et al's study reported that d w is a function of patient weight, suggesting that the calculation of SSDEs could be simplified using weight [20,21]. To the best of our knowledge, there have been no previous studies on the calculation of SSDE from the chest and abdomen-pelvic CT examinations based on the correlations of body weight, BMI, and d w .…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy achieved in the SSDE and D W computations and the very small time for processing an entire CT study allow us to compute the water-equivalent diameter averaged over the slice D w_ave ( 17 ), a quantity favorable for protocol optimization ( 17 ). Based on the authors’ knowledge, there are no previous studies showing such small computational times allowing for clinical real-time computation of size-specific dosimetric quantities.…”
Section: Discussionmentioning
confidence: 99%
“…Automatic noise calculation performed directly from the patient image is an important factor to optimize the radiation dose received by the patient. Automated dose calculation received by patients using the concept of size-specific dose estimate (SSDE) has been widely reported [15,[26][27][28]. While automated noise calculations performed directly from patient images have been reported previously [20,24], they have been limited to certain body parts such as the abdomen or thorax.…”
Section: Discussionmentioning
confidence: 99%